Emerging Technologies Applied to Learning Helps students with Disabilities - Seguí, Ignacio; Garcia, A. (Edulearn12: 4TH International Conference on Education and New Learning Technologies, 2020)
Since 2006, when the European Commission identified and recommended eight key competences for lifelong learning, education has commenced a continual shift in which emerging technologies have a key role. However, the incorporation of new technology can be a barrier for students with disabilities. Therefore, the identification of technologies that allow access for all is essential to respect the principle of equal opportunities. This paper identifies emerging technologies that are already developed and are applicable to pre-university education respecting the principle of access to education for all. For this identification, attention is primarily focused on the Horizon K-12 Edition reports, published since 2009, and aims to offer a vision of a panel of experts on the impact of new technologies in pre-university education. After the analysis of sixteen technologies, four were identified that are at a mature stage of development and have successful experiences of use but have not been fully incorporated, becoming currently emerging technologies for pre-university education. These four groups are: (1) GBL (Game-Based Learning), (2) LA (Learning Analytics), (3) PLE (Personal Learning Environments), (4) Mobile Computing and Mobile Networks. A technological model is implemented on the four groups, which focuses on integrated accessibility as a fundamental criterion for the selection of the technologies that make up the model. A PLE is the core of the proposed model, being the perfect complement for integration in schools, providing student-based learning and following the recommendations of the Commission, where schools must help students to take responsibility for their own learning and personal development throughout their lives. A PLE should be modeled to be accessible to all. One approach is presented in this paper based on PLE-accessible and open-source software. The PLE is the core integrator of tools, thus the use of Elgg software is proposed, which enables advanced interactivity services with peers, teachers and even family members. Integrated with Elgg, ATutor is proposed as LCMS (Learning Content Management System), being the only LCMS that focuses on accessibility. The model can be complemented by a collection of tools that are distinguished by their versatility: Wookie, enables widgets tailored to requirements to be generated; (GBL), for its ability to be integrated within the LCMS; qTwitter, as an accessible tool for twitter; Zoho, as an office suite in the cloud; YourDraft, as an online collaborative What You See What You Get type text editor. The emerging tools identified have great potential for use in improving learning processes: they comply with the current paradigm of learning skills, they can be collaborative, addresses the option of informal learning, they are ubiquitous, technologically advanced, motivating and, above all, respect the principle of equal opportunities and reinforce the acquisition of key competences defined for European students.
Keywords: e-learning; PLE; Personal Learning Environments; disabilities; primary education; secondary education; pre-university education; k12; WOS(2)